Capital-Labor Substitution, Structural Change and the Labor Income Share - Francisco Alvarez-Cuadrado; Ngo Van Long; Markus Poschke (Institute for the Study of Labor (IZA), 2015)
Recent work has documented declines in the labor income share in the United States and beyond. This paper documents that these trends differ between manufacturing and services in the U.S. and in a broad set of other industrialized economies, and shows that a model where the degree of capital-labor substitutability differs across sectors is consistent with these trends. We calibrate the model exploiting additional information on the pace of structural change from manufacturing to services, on which the model also has predictions. We then conduct a decomposition to establish the relative importance of several potential drivers of changes in factor income shares and structural change that have been proposed in the literature. This exercise reveals that differences in productivity growth across sectors, combined with differences in substitution possibilities, have been the main driver of both changes in the labor income share and structural change.
Keywords: O40; O41; O30; 330; structural change; labor income share; capital-labor substitution